Pengaruh Kombinasi Jus Buah Belimbing Wuluh (Averrhoa blimbi, L.) dan Mentimun (Cucumis sativus, L.) terhadap Tekanan Darah dan Kolesterol Total pada Lansia Hipertensi - Tiawati, Sulis; Putriningtyas, Natalia Desy (Universitas Negeri Semarang, 2023)
Hypertension is still a major problem in the world. Hypertension is related to total cholesterol levels where the narrowing and stiffness of the blood vessel walls causes blood pressure to increase. Non-pharmacological therapy by consuming foodstuffs that contain potassium, for example, blimbi and cucumber. This study aims to determine the effect of giving a combination of blimbi juice and cucumber on blood pressure and total cholesterol in elderly hypertensives in Patapan Village, Cirebon Regency. This study used Quasy Experimental Design using a pre-post test with control group approach. Sampling using purposive sampling totaling 22 people each in the intervention group and the control group. The combination of blimbi juice and cucumber is taken in the morning for 7 days in a row with a dose of 300 ml. After giving a combination of blimbi juice and cucumber in the intervention group, the average blood pressure decreased by 151.95/86.68mmHg and cholesterol 222.05mg/dL and in the control group the average was 148.95/87.91mmHg mmHg. and total cholesterol 214.77 mg/dL. Based on the independent t test, the p value of systolic blood pressure was 0.047 (<0.05) and diastolic 0.201 (>0.05) and total cholesterol 0.046 (<0.05). This means that there is a significant difference in effect on systolic blood pressure and there is no significant effect on diastolic blood pressure and there is a significant effect on total cholesterol.